Resonant auger decay of the core-excited C*O molecule in intense x-ray laser fields - Demekhin, Philipp V.; Chiang, Ying-Chih; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2011)
The dynamics of the resonant Auger (RA) process of the core-excited C∗O(1s−1π∗,vr=0) molecule in an intense x-ray laser field is studied theoretically. The theoretical approach includes the analog of the conical intersections of the complex potential energy surfaces of the ground and “dressed” resonant states due to intense x-ray pulses, taking into account the decay of the resonance and the direct photoionization of the ground state, both populating the same final ionic states coherently, as well as the direct photoionization of the resonance state itself. The light-induced nonadiabatic effect of the analog of the conical intersections of the resulting complex potential energy surfaces gives rise to strong coupling between the electronic, vibrational, and rotational degrees of freedom of the diatomic CO molecule. The interplay of the direct photoionization of the ground state and of the decay of the resonance increases dramatically with the field intensity. The coherent population of a final ionic state via both the direct photoionization and the resonant Auger decay channels induces strong interference effects with distinct patterns in the RA electron spectra. The individual impact of these physical processes on the total electron yield and on the CO+(A2Π) electron spectrum are demonstrated.
Im Titel ist [ast] als Tropfensternchen dargestellt
Gesehen am 05.05.2022